Why development aid? - STREETEN, P. (PSL Quarterly Review, 2013)
It has become common practice for both bilateral donors and multilateral aid agencies to make loans to developing countries below the commercial rate of interest. One obvious reason for this is the competition for exports, which can lead to subsidised credits in the hope that export sales of manufactured products or sales of surplus agricultural commodities are thereby promoted. The boundaries become a bit blurred when subsidised loans are given for infrastructure that makes private foreign investment more profitable, or loans to promote benefits from trade in the long-term. The present work, however, focuses on loans without any clear commercial qui pro quo. The author presents five arguments. JEL: F21, F35